Densities and Excess Volumes of Binary Liquid Mixtures of PEG 200, PEG 400 and PEG 600 with Toluene at Three Temperature - Sharma, R.A.; Vora, D.N. (Asian Journal of Chemistry, 2010)
Densities for the systems PEG 200 + toluene, PEG 400 + toluene and PEG 600+ toluelne at three different temperatures have been studied. Excess volumes (VE) are calculated over the entire range of composition at three different temperatures using the standard relation. The data are fitted into an empirical equation. VE = X1X2[a + b(2X1 - 1) + c(2X1 - 1)2] and the values of constants a, b and c are evaluated by the least squares method along with standard deviation σ. The marked reduction in (VE) with increase in C—C chain length of PEG has been studied in the light of interaction phenomena.